2021
DOI: 10.1002/adem.202100095
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Micromechanics of Organic Aerogels Based on Experimental and Modeling Results

Abstract: While the characteristics of the macroscopic mechanical behavior of organic aerogels are well known, the mechanisms responsible for the substructural evolution of their networks under mechanical deformation are not fully understood. Herein, organic aerogels from the aqueous sol−gel polymerization of resorcinol with formaldehyde are first prepared. Specifically, the resorcinol to water (R:W) molar ratio is varied for obtaining diverse highly open‐cellular porous structures with mean pore sizes ranging between 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…This may lead to one order of magnitude increase in the modulus (Figure 4). [34][35][36] Synthetic polymer aerogels, for example, based on resorcinolformaldehyde, are not brittle and follow foam-like stress-strain dependence (Figure 4b); [37] similar trends were reported for other polymer aerogels. [33,38,39] Compressive modulus of synthetic polymer aerogels can reach several tens of MPa at density around 0.1-0.2 g cm À3 .…”
Section: (C)supporting
confidence: 74%
See 1 more Smart Citation
“…This may lead to one order of magnitude increase in the modulus (Figure 4). [34][35][36] Synthetic polymer aerogels, for example, based on resorcinolformaldehyde, are not brittle and follow foam-like stress-strain dependence (Figure 4b); [37] similar trends were reported for other polymer aerogels. [33,38,39] Compressive modulus of synthetic polymer aerogels can reach several tens of MPa at density around 0.1-0.2 g cm À3 .…”
Section: (C)supporting
confidence: 74%
“…Illustration of the mechanical properties of aerogels: a) compressive modulus of various aerogels as a function of density (TAB is 1,3,5-benzenetricarbonyl trichloride, POSS is polyhedral oligomeric silsesquioxane), data taken from;[20,35,97,118] b) stress-strain curves stress-strain for resorcinol-formaldehyde aerogels under compression displaying the dependence on the resorcinol (R):water (W) ratio. Reproduced with permission [37]. Copyright 2021, The Authors, published by Wiley-VCH.…”
mentioning
confidence: 99%
“…Dargazany and Itskov [13,14] studied the mechanical behavior of interconnected arrays of colloidal particles assuming that at the touching points the bonds can be described as non-linear springs. In many aerogels, the network of particles consist of moderately up to heavily connected bonds and therefore the Gibson and Ashby [1] model has been applied for aerogels [5,15]. All studies performed so far have shown that the pore collapse occurs as a result of a critical stress arising from buckling or bending of the pore walls or better the connected struts.…”
Section: Introductionmentioning
confidence: 99%
“…[43,63] The value for α derived from the current dataset is 4.3, somewhat higher than the previously reported for silica aerogels, e.g., 3.6 [43] and 3.7 [63] from experiments or 3.61 from simulations, [64] and significantly higher than what is typical for many other aerogel systems, e.g., 1.75 for alumina aerogels, [60] 1.8 for cellulose aerogels, [61] or 2.7-3.7 for resorcinol-formaldehyde aerogels. [65,66] The E-modulus of the 2 h-aged aerogels is lower by a factor of 1.5-2.5 compared with the 24 h-aged counterparts of similar density, a direct consequence of the formation of thicker interparticle necks during the extended aging time, which increases the structural strength to the aerogel network. [35] Many industries use secant moduli σ 10 , σ 30 , σ 50 , and σ 80 , [67] i.e., the stress values for a given percentage of strain, rather than E-moduli to describe the sample deformation under stress.…”
Section: E-modulus and σ Xmentioning
confidence: 99%